Non-coding polymorphisms in nucleotide binding domain 1 in ABCC1 gene associate with transcript level and survival of patients with breast cancer - Kunická, Tereza; Václavíková, Radka; Hlaváč, Viktor; Vrána, David; Pecha, Václav; Rauš, Karel; Trnková, Markéta; Kubáčková, Kateřina; Ambruš, Miloslav; Vodičková, Ludmila; Vodička, Pavel; Souček, Pavel (PloS one, 2014)
OBJECTIVES: ATP-Binding Cassette (ABC) transporters may cause treatment failure by transporting of anticancer drugs outside of the tumor cells. Multidrug resistance-associated protein 1 coded by the ABCC1 gene has recently been suggested as a potential prognostic marker in breast cancer patients. This study aimed to explore tagged haplotype covering nucleotide binding domain 1 of ABCC1 in relation with corresponding transcript levels in tissues and clinical phenotype of breast cancer patients. METHODS: The distribution of twelve ABCC1 polymorphisms was assessed by direct sequencing in peripheral blood DNA (n = 540). RESULTS: Tumors from carriers of the wild type genotype in rs35623 or rs35628 exhibited significantly lower levels of ABCC1 transcript than those from carriers of the minor allele (p = 0.003 and p = 0.004, respectively). The ABCC1 transcript levels significantly increased in the order CT-GT>CC-GT>CC-GG for the predicted rs35626-rs4148351 diplotype. Chemotherapy-treated patients carrying the T allele in rs4148353 had longer disease-free survival than those with the GG genotype (p = 0.043). On the other hand, hormonal therapy-treated patients with the AA genotype in rs35628 had significantly longer disease-free survival than carriers of the G allele (p = 0.012). CONCLUSIONS: Taken together, our study shows that genetic variability in the nucleotide binding domain 1 has a significant impact on the ABCC1 transcript level in the target tissue and may modify survival of breast cancer patients.
Keywords: senioři; analýza přežití; nádory prsu; messenger RNA; Middle Aged; ženské pohlaví; Breast Neoplasms; RNA, Messenger; Humans; jednonukleotidový polymorfismus; proteiny spojené s mnohočetnou rezistencí k lékům; Aged; Female; Survival Analysis; Multidrug Resistance-Associated Proteins; lidé; Polymorphism, Single Nucleotide; lidé středního věku